Pronounced Trace Element Variation in Follicular Fluids of Subfertile Women Undergoing Assisted Reproduction - Lilly Johanna Schmalbrock (MDPI AG, 2021)
Female subfertility is a growing concern, especially in view of an increasing prevalence of polycystic ovary syndrome (PCOS). Assisted reproductive technologies (ART) offer a perspective for pregnancy, but the outcome rate is still suboptimal. The trace elements (TE), copper (Cu), selenium (Se), and zinc (Zn) are essential for fertility and development. We hypothesized that TE concentrations are related to oocyte quality and growth and affect pregnancy outcomes in women undergoing ART. Concentrations of TE were measured by total reflection X-ray fluorescence. Extracellular glutathione peroxidase 3 (GPX3) and selenoprotein P (SELENOP) were determined as additional Se biomarkers. Corresponding serum and follicular fluid (FF) samples were available from women with (n = 20) and without (n = 20) PCOS diagnosis undergoing hormone treatment within the ART procedure, respectively, and FF samples were classified into five groups based on morphological assessment. Serum showed higher TE concentrations than FF, and TE levels correlated positively between both matrices. Individual FF from the same women showed surprisingly high variability in TE concentration, and follicles without oocytes displayed the lowest TE concentrations. Both Se biomarkers GPX3 and SELENOP were present in FF and correlated positively to Se concentrations. Some notable relationships were observed between morphokinetic parameters, TE concentrations, and GPX3 activity. A slightly depressed serum Zn concentration was observed in PCOS. Our results indicate a direct relationship between TE in serum and FF, positive correlations between the three Se biomarkers in FF, and high variability between the FF from the same woman with the lowest TE concentrations in the follicles with the poorest quality. The differences observed in relation to PCOS diagnoses appear relatively minor. Collectively, the data support the notion that TE assessment of follicles may contribute to optimal oocyte selection and subsequently influence ART success.